Indicators of Mineral Metabolism Depending on the Body Mass Index - Marshinskaia , Olga; Kazakova, Tatiana; Notova, Svetlana; Gedulianov, Marat (KnE Life Sciences, 2021)
n this study, the elemental status of the hair of adolescent girls in the Orenburg region (n=120) with different levels of body mass index was studied and their average daily diet was evaluated. A nutrition assessment program was used to study the diet. Estimation of the element status was carried out through the study of the chemical composition of the hair by ICP-AES and ICP-MS. It was found that there was a general imbalance of elements in the diet of all of the studied groups, and students with obesity had lower consumption levels of all elements, except Mg and Se. Similarly, obese students had lower levels of all elements in their hair except Se, P, and Zn. Thus, changes in the level of body mass index, as well as geochemical features of the territory of the Orenburg region, affect the content of most macro- and microelements. Keywords: metabolic syndrome, trace elements, body mass index